Стресс-мусобақалашув жараёнидаги психологик элементлардан бири сифатида (волейболчилар мисолида) - Эгамбердиев Илхом Эргашевич, Турсунпўлатова Малика (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article reflects the psychological characteristics of an athlete in competitions and emphasizes the enormous scientific and practical importance of studying the psychological characteristics of an athlete’s personality.